Use of the English urgent referral pathway for suspected cancer and mortality in patients with cancer: cohort study. (13th October 2015) - Møller, Henrik; Gildea, Carolynn; Meechan, David; Rubin, Greg; Round, Thomas; Vedsted, Peter
Abstract : Objective To assess the overall effect of the English urgent referral pathway on cancer survival. Setting 8049 general practices in England. Design Cohort study. Linked information from the national Cancer Waiting Times database, NHS Exeter database, and National Cancer Register was used to estimate mortality in patients in relation to the propensity of their general practice to use the urgent referral pathway. Participants 215 284 patients with cancer, diagnosed or first treated in England in 2009 and followed up to 2013. Outcome measure Hazard ratios for death from any cause, as estimated from a Cox proportional hazards regression. Results During four years of follow-up, 91 620 deaths occurred, of which 51 606 (56%) occurred within the first year after diagnosis. Two measures of the propensity to use urgent referral, the standardised referral ratio and the detection rate, were associated with reduced mortality. The hazard ratio for the combination of high referral ratio and high detection rate was 0.96 (95% confidence interval 0.94 to 0.99), applying to 16% (n=34 758) of the study population. Patients with cancer who were registered with general practices with the lowest use of urgent referral had an excess mortality (hazard ratio 1.07 (95% confidence interval 1.05 to 1.08); 37% (n=79 416) of the study population). The comparator group for these two hazard ratios was the remaining 47% (n=101 110) of the study population. This result in mortality was consistent for different types of cancer (apart from breast cancer) and with other stratifications of the dataset, and was not sensitive to adjustment for potential confounders and other details of the statistical model. Conclusions Use of the urgent referral pathway could be efficacious. General practices that consistently have a low propensity to use urgent referrals could consider increasing the use of this pathway to improve the survival of their patients with cancer.